2015
DOI: 10.1128/mcb.01091-14
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Transcription Factor EB-PGC1α Axis by Beclin-1 Controls Mitochondrial Quality and Cardiomyocyte Death under Stress

Abstract: In cardiac ischemia-reperfusion injury, reactive oxygen species (ROS) generation and upregulation of the hypoxia-inducible protein BNIP3 result in mitochondrial permeabilization, but impairment in autophagic removal of damaged mitochondria provokes programmed cardiomyocyte death. BNIP3 expression and ROS generation result in upregulation of beclin-1, a protein associated with transcriptional suppression of autophagy-lysosome proteins and reduced activation of transcription factor EB (TFEB), a master regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 58 publications
2
75
0
1
Order By: Relevance
“…Indeed, we have previously found that transcriptional suppression of the autophagy machinery with reperfusion-induced accumulation of BECN1 explains the lack of a protective role of the observed extent of autophagy induction in cardiac ischemia-reperfusion injury. 36,68 Further insights into this process could be gleaned via careful examination of the effects of intermittent fasting on the transcriptional program of the injured myocardium, in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, we have previously found that transcriptional suppression of the autophagy machinery with reperfusion-induced accumulation of BECN1 explains the lack of a protective role of the observed extent of autophagy induction in cardiac ischemia-reperfusion injury. 36,68 Further insights into this process could be gleaned via careful examination of the effects of intermittent fasting on the transcriptional program of the injured myocardium, in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviral particles for shRNA targeting Becn1 (shBecn1), 68 shLacZ and exogenous expression of human TFEB have been previously described. 77 Generation of conditional cardiac Tfeb transgenic mice The coding sequence of mouse Tfeb (translated from transcript variant 2, NP_001155194.1, that encodes a protein similar in size to human TFEB) with a N-terminal FLAG tag was cloned into the a-Myosin Heavy Chain promoter -TetOMin construct generously provided by Jeffery Robbins, Cincinnati Children's Hospital.…”
Section: Studies With Nrcmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Myocardial Ischemia Reperfusion Studies-The methods of Weinheimer et al (60) were used. Mice were subjected to reversible left anterior descending (LAD) coronary artery occlusion to induce ischemia for 30 min, followed by 24 h of reperfusion.…”
Section: Mass Spectrometric Analyses Of Eicosanoids Docosanoids Andmentioning
confidence: 99%